Implementasi Pendidikan Karakter Dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Kadek Hengki Primayana (Cetta: Jurnal Ilmu Pendidikan, 2022)
This study describes the implementation of character education in Indonesian language learning, including planning, implementation, and assessment. This research is descriptive research with a qualitative approach. The results obtained in this study are that character education in learning Indonesian content at SDN 2 Tukadmungga has been carried out both in planning, implementing, and assessing learning but not all of it has been implemented because it is still in the covid-19 pandemic. At the learning planning stage, the teacher has entered the character values that will be applied in learning in the syllabus and lesson plans. The implementation of learning Indonesian content at SDN 2 Tukadmunga is enough to be carried out through online learning via WhatsApp. Assessment of Indonesian language content learning includes effective assessment.